2019
DOI: 10.1016/j.afjem.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and diagnostic work up of suspected pulmonary embolism in a district hospital emergency centre serving a high HIV/TB burden population

Abstract: IntroductionThe diagnosis of pulmonary embolism (PE) is challenging to make and is often missed in the emergency centre. The diagnostic work-up of PE has been improved by the use of clinical decision rules (CDRs) and CT pulmonary angiography (CTPA) in high-income countries. CDRs have not been validated in the South African environment where HIV and tuberculosis (TB) are highly prevalent. Both conditions are known to induce a hyper-coagulable state. The objective of this study was to describe the clinical prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…5,6,7,9 This is in keeping with other literature on HIV-infected patients where the mean ages for PE were younger than the general population, ranging from 40 to 45 years. 2,3,10,11,12 Presenting symptoms in this study were typical of that described in the Prospective Investigation of Pulmonary Embolism Diagnosis (PIOPED II) trial, including shortness of breath, syncope, chest pain and haemoptysis -all of which are non-specific. 13 The CTPA prevalence of PE in an HIV-infected study population in this study was found to be 35%.…”
Section: Discussionmentioning
confidence: 59%
“…5,6,7,9 This is in keeping with other literature on HIV-infected patients where the mean ages for PE were younger than the general population, ranging from 40 to 45 years. 2,3,10,11,12 Presenting symptoms in this study were typical of that described in the Prospective Investigation of Pulmonary Embolism Diagnosis (PIOPED II) trial, including shortness of breath, syncope, chest pain and haemoptysis -all of which are non-specific. 13 The CTPA prevalence of PE in an HIV-infected study population in this study was found to be 35%.…”
Section: Discussionmentioning
confidence: 59%
“…12 Clinical prediction rules such as Well's and Geneva criteria to determine pretest probability for PE are validated in well-resourced countries but seem to fall short in terms of applicability in low resource settings. 7,13 Clinical prediction rules have also been shown to be unreliable in pregnancy where D-dimer had a sensitivity of 88.4% and low specificity of 8% using a standard cut off. 14 Multiple studies have been conducted to determine the diagnostic accuracy of the d-dimer assay in diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…6 The diagnosis of pulmonary embolism in resource limited settings may be challenging as evidenced by the search for clinical decision rules by various set ups. 7 The D-dimer is a breakdown product of the cross linked fibrin mesh and can be used to rule out pulmonary embolism in patients with low pretest clinical probability based on specified cut off levels e.g 1000ng/ml. 6 This finding has also been found to be true in children.…”
Section: Introductionmentioning
confidence: 99%
“…CTPA is the gold standard for diagnosing PE [16]. However, there may be financial and logistic limitations in accessing CTPA especially in resource restrained settings, with the added challenge of exposure of technicians to COVID-19 patients [13,28]. These hindrances may lead to delayed/missed diagnosis and increased chances of mortality.…”
Section: Discussionmentioning
confidence: 99%